A Comparative Study of Assay Performance of Commercial Hepatitis E Virus Enzyme-Linked Immunosorbent Assay Kits in Australian Blood Donor Samples. (7th November 2016) - Shrestha, Ashish C.; Flower, Robert L. P.; Seed, Clive R.; Stramer, Susan L.; Faddy, Helen M.
Abstract : Hepatitis E virus (HEV) is transfusion-transmissible and therefore poses a risk to blood transfusion safety. Seroprevalence studies are useful for estimating disease burden and determining risk factors. Considerable variability in the sensitivity of HEV antibody detection assays exists. This study aimed to compare the performances of commercially available HEV enzyme-linked immunosorbent assays (ELISA) in Australian blood donor samples. Plasma samples that tested positive (n = 194 ) or negative (n = 200 ) for HEV IgG (Wantai HEV IgG ELISA) were selected. Of the 194 HEV IgG positive samples, 4 were positive for HEV IgM (Wantai HEV IgM ELISA). All samples were tested with the MP Diagnostics: HEV IgG ELISA, total (IgG, IgM, and IgA) HEV antibody ELISA, and HEV IgM ELISA. Of the 194 Wantai HEV IgG positive samples, 92 (47%) tested positive with the MP Diagnostics HEV IgG ELISA (κ = 0.47 ) and 126 (65%) with MP Diagnostics total HEV antibody assay (κ = 0.65 ). There was poor agreement between Wantai and MP Diagnostics HEV IgM assays. This study demonstrated poor agreement between the assays tested. These observations are consistent with previous reports demonstrating significant variability between HEV ELISAs, highlighting that results of HEV serology should be interpreted with caution.